2016
DOI: 10.1111/eva.12358
|View full text |Cite
|
Sign up to set email alerts
|

Intense selective hunting leads to artificial evolution in horn size

Abstract: The potential for selective harvests to induce rapid evolutionary change is an important question for conservation and evolutionary biology, with numerous biological, social and economic implications. We analyze 39 years of phenotypic data on horn size in bighorn sheep (Ovis canadensis) subject to intense trophy hunting for 23 years, after which harvests nearly ceased. Our analyses revealed a significant decline in genetic value for horn length of rams, consistent with an evolutionary response to artificial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
268
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(280 citation statements)
references
References 49 publications
9
268
3
Order By: Relevance
“…In bighorn sheep, a decline in breeding values appeared to account for nearly 20% of the overall decrease in horn size observed over 23 years (figure 1). The study population doubled in size during the study, leading to a large density-dependent decrease in horn size [6]. The same absolute evolutionary effect on horn size, extended over a longer period of intense selective hunting, however, may well explain most of the declines seen in other mountain sheep populations where density has not changed substantially [7,18,33].…”
Section: Does Harvest-induced Evolution Happen?mentioning
confidence: 84%
See 1 more Smart Citation
“…In bighorn sheep, a decline in breeding values appeared to account for nearly 20% of the overall decrease in horn size observed over 23 years (figure 1). The study population doubled in size during the study, leading to a large density-dependent decrease in horn size [6]. The same absolute evolutionary effect on horn size, extended over a longer period of intense selective hunting, however, may well explain most of the declines seen in other mountain sheep populations where density has not changed substantially [7,18,33].…”
Section: Does Harvest-induced Evolution Happen?mentioning
confidence: 84%
“…Available long-term time series on harvested mammals tend to focus instead on body mass and on the size of male weapons such as horns, antlers and tusks (table 1) [7,11]. In addition, unlike in wild fish, a few longterm studies of terrestrial mammals have established deep pedigrees and measured both trait heritability and selection in the wild, although rarely in hunted populations [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…The short answer appears to be “yes,” at least in some cases, in that a large number of studies have demonstrated adaptive evolution over time frames ranging from years to decades (reviewed in Reznick & Ghalambor, 2001; Hendry, Farrugia, & Kinnison, 2008). Such contemporary evolutionary responses have been observed in response to hunting/harvesting (Coltman et al., 2003; Pigeon, Festa‐Bianchet, Coltman, & Pelletier, 2016), pollution (Antonovics, Bradshaw, & Turner, 1971; Levinton et al., 2003), introduced species (Strauss, Lau, & Carroll, 2006), novel and changing climates (Bradshaw & Holzapfel, 2001; Colautti & Barrett, 2013; Merilä & Hendry, 2014), and novel environments (Prentis, Wilson, Dormontt, Richardson, & Lowe, 2008). At the same time, however, many other populations that have faced environmental change clearly did not evolve rapidly enough, as evidenced by frequent extirpations and extinctions (Barnosky et al., 2011; Hughes, Daily, & Ehrlich, 1997).…”
Section: Intraspecific Variation Is Critical For Population Dynamicsmentioning
confidence: 99%
“…For instance, many long‐term studies have tracked changes in mean phenotypes to infer the effects of disturbances such as in fisheries (Kuparinen & Merilä, 2007), hunting (Coltman et al., 2003; Pigeon et al., 2016), or with climate change (Parmesan, 2006). Some studies have also shown changes in trait variance, such as declining variance in body size over nine decades in fished cod populations (Olsen, Carlson, Gjøsaeter, & Stenseth, 2009).…”
Section: Toward a Monitoring System For Intraspecific Variationmentioning
confidence: 99%
See 1 more Smart Citation